What Is the Cost of Providing Outpatient HIV Counseling and Testing and Antiretroviral Therapy Services in Selected Public Health Facilities in Nigeria? - Aliyu, H.B.; Chuku, N.N.; Torpey, K.; et al. (J Acquir Immune Defic Syndr, 2012)
Background: Limited data on actual cost of providing HIV/AIDS services in Nigeria makes planning difficult. A study was conducted in 9 public health facilities supported by the Global HIV/AIDS Initiative Nigeria. The objective was to determine the cost of outpatient HIV Testing and Counseling (HTC) and antiretroviral therapy (ART) services per patient. Methods: Two tertiary and 7 secondary facilities were purposively selected across the six geopolitical regions. Facilities were distrib uted in urban and rural settings. Utilization and cost data for a 12-month period (January to December 2010) were analyzed. Cost elements included consumables, human resources, infrastructure, trainings, facility management, and Global HIV/AIDS Initiative Nigeria technical support. Total costs were apportioned based on percentage utilization by services, and unit costs were derived by dividing resource inputs by service outputs. Data were analyzed using Microsoft Excel 2003. A sensitivity analysis was also conducted for key assumptions. Results: Mean costs for HTC and ART were US $7.4 and US $209.0, respectively. Costs were higher in Northern facilities (US $6.9, US $250.8), compared with Southern ones (US $6.7, US $194.7); and in tertiary facilities ($18.5, $338.4), compared with secondary ones ($6.3, $204.9). Major cost drivers for HTC and ART were human resources—ranging from 62% to 50%, and ARV drugs —ranging from 54% to 31%, respectively.
Research Article
Keywords: cost; HTC; ART